Transfer effects in task-set cost and dual-task cost after dual-task training in older and younger adults: further evidence for cognitive plasticity in attentional control in late adulthood. - Bherer L; Kramer AF; Peterson MS; Colcombe S; Erickson K; Becic E (Experimental Aging Research)
Older adults' difficulties in performing two tasks concurrently have been well documented (Kramer & Madden, 2008). It has been observed that the age-related differences in dual-task performance are larger when the two tasks require similar motor responses (2001) and that in some conditions older adults also show greater susceptibility than younger adults to input interference (Hein & Schubert, 2004). The authors recently observed that even when the two tasks require motor responses, both older and younger adults can learn to perform a visual discrimination task and an auditory discrimination task faster and more accurately (Bherer et al., 2005). In the present study, the authors extended this finding to a dual-task condition that involves two visual tasks requiring two motor responses. Older and younger adults completed a dual-task training program in which continuous individualized adaptive feedback was provided to enhance performance. The results indicate that, even with similar motor responses and two visual stimuli, both older and younger adults showed substantial gains in performance after training and that the improvement generalized to new task combinations involving new stimuli. These results suggest that dual-task skills can be substantially improved in older adults and that cognitive plasticity in attentional control is still possible in old age.